História de vida de Limnoctites rectirostris (aves: furnariidae) nos campos de cima da serra, sul do Brasil - Larre, Gabriel Guimarães (2017)
Straight-billed Reedhaunter belongs to Furnariidae that has extreme restriction in relation to habitat use, being found only in wetlands areas with the abundance of Apiaceae Eryngium pandanifolium, depending exclusively on this type of environment to forage and breed. Information on life history of this species and, especially on its breeding biology are very scarce, and all the studies of Straight-billed Reedhaunter were conducted on Argentine and Uruguayan populations. Our objective was to estimate the period and breeding success of Limnoctites rectirostris, in addition to analyzing its reproductive activity, such as nesting activity, nest construction time, incubation time, nest size and brood size. Additionally we determine the limits of the breeding territories of couples of Straight-billed Reedhaunter. We studied a population in the northeast of Rio Grande do Sul, in an ecosystem associated with the Atlantic Forest biome, known as upland grasslands, more specifically between two municipalities, Bom Jesus and Jaquirana, in the surroundings and inside the Tainhas state park. We did fieldwork on three breeding seasons (from September to January) of 2012-2013, 2015-2016 and 2016-2017, totalizing about 15 months of sample effort. We monitored 85 nests during these seasons, estimating the breeding season in about 5.3 months (160 days). The breeding activity was strongly correlated with the photoperiod (rs=0.69; P=0.0007), being recorded the apex of the nesting activity during the last week of November. The average time of nest building, incubation and nestling was, respectively, 6.2 ± 1.3, 17 ± 1.18 and 16.43 ± 0.97 days. Clutch size was estimated in 2.7 ± 0.46, which the most frequently brooding (70%) had three eggs. The rate of egg eclosion was 78% and the annual productivity of fledging 22%. Nest survival was modeled with program MARK that estimated 10.51% while with Mayfield method and apparent success were 12.8% and 17.4% respectively. The interaction between the constant temporal tendency with nest height in relation to ground and plant height support generated the best model (AICc=292.958), which explain nest survival. Predation was the main cause of brooding lost (65.3%), presenting greater during egg phase (60%) than in the nestling period (40%). We identify Philodrias olfersi and Licalopex gimnocercus as potential nest predators. Cryptonanus guahybae was registered visiting nests during the night, inactivating and utilizing them during day as shelter, suggesting an interaction besides the predation. We captured and marked with unique sequences of colored plastic and metallic rings, 78 individuals during the three breeding seasons studied, besides that we measured and determined the limits of 34 breeding territories. The method that best reflected the reality of L. rectirostris territories was the Fixed-Kernel Technique with the Least Square Cross Validation smoothing parameter, which generated area values between 0.51 and 11.16 ha, with an average of 3.33 ± 2.1 ha. The border of the territories coincides with the limits of the wetlands areas with abundance of E. pandanifolium, showing the strong habitat restriction of the species studied. The comparison between specific nesting sites and control plots presented significant difference (P < 0.05) in almost all measured variables, demonstrating that Straight-billed Reedhaunter chose sites with lower vegetation height, higher soil exposed and lower strata of vegetation, less vegetation densification, as well as less distance from the border of the plains than the control plots measured within the breeding territories. Probably this selection of nesting sites is a response to the selective pressure imposed by the main cause of brood-losses, the small marsupial Cryptonanus guaybae, which in addition to predating the eggs, uses the nest as a shelter.